ADAPTASI FLEKSIBILITAS SISTEM INFORMASI MANAJEMEN PENGELOLAAN RUMAH SUSUN SEDERHANA SEWA (RUSUNAWA) UNIVERSITAS TANJUNGPURA - Hamida Hamida; Novi Safriadi; Anggi Perwitasari (Universitas Lampung, 2023)
The provision of information at Rusunawa Untan has increased in response to the needs of students for registration and data management. However, the system currently in use is still conventional and ineffective. This research aims to develop a web-based information system to manage registration and data at Rusunawa Untan. This system can send WhatsApp messages to residents and adapt to user needs. The flexibility of the information system is crucial in its development as the business environment is constantly changing. This research explains the development of the flexibility of the information system and the objectives to be achieved. The Object Oriented Analysis Design (OOAD) method is used for needs analysis, UML design, and implementation with PHP and the Laravel framework. The application is tested using black box method and User Acceptance Test (UAT) with 23 respondents. The UAT results show a satisfaction rate of 85.30%, indicating that the application meets expectations. The OOAD method is well implemented, and the application is well-received and able to adapt to changes in business requirements without significant modifications to the system.